Panchayat and colonialism in Humayun Kabir's Men and Rivers - Hasan, Md. Mahmudul (Routledge, 2024)
Bengali peasants, as portrayed in Humayun Kabir’s 1945 novel Men and Rivers, have admirable notions of morality and justice, epitomized by the indigenous panchayat (village council/court) system. Written against the backdrop of peasant movements and anti-colonial struggles in Bengal, the novel implicitly provides an economic and cultural critique of British rule in the region. This article situates the text in colonial Bengal and the peasant revolutions of the 1930s. Referring to Frantz Fanon’s valorization of the peasants, it discusses Kabir’s depiction in Men and Rivers of the simplicity, integrity, and altruism of the peasantry as opposed to the sleaze and hypocrisy of colonialism and colonial modernity. It juxtaposes panchayat and colonialism to show the native peasants’ egalitarian potential and the encroaching colonizers’ exploitative motives, looks at Kabir’s celebration of rural traditions, and compares the South Asian panchayat system to its African counterparts – djemaas in northern, and kgotla in southern, Africa.